Genetic instability in cervical cancer detected by arbitrarily primed polymerase chain reaction - Rujinee Paditaporn (2018)
The genetic instability in 54 Thai cervical cancer tissues were analyzed by Arbitrarily Primed Polymerase Chain Reaction (AP-PCR). The band alterations produced from 54 arbitrary primers were compared between the DNA finger printing from the patients and their corresponding normal cervical tissues. Results revealed 7 arbitrary primers provided DNA alteration patterns. Of these, an allelic loss in tumor DNA was found in DNA fingerprinting obtained from primers F-2 (64.8%), F-11 (68.5%), U-8 (51.9%), AE-3 (75.9%), AE-11 (53.7%), respectively. Moreover, DNA amplification was exhibited in patterns with primers B-12 (42.6%), J-16 (24.1%) and U-8 (70.4%). When genetic instability was investigated for associations with clinicopathological features, only the DNA amplified fragment with primer U-8 was significantly associated with stage II (P=0.030). Likewise, allelic loss amplified from arbitrary primer AE-3 showed significantly associate with age lower than 50 years old (P=0.003). Our findings suggest that the DNA alteration fragments produced from arbitrary primers of U-8 and AE-11 might be relevant to the pathogenesis of cervical cancer in Thai patients.